2022
DOI: 10.1111/1759-7714.14375
|View full text |Cite
|
Sign up to set email alerts
|

CAR‐T cell therapy for lung cancer: Potential and perspective

Abstract: Lung cancer is the highest incidence and mortality of all cancers around the world. In the present immunotherapy era, an increasing number of immunotherapeutic agents including monoclonal antibody-targeted drugs have been used in the clinical treatment of malignancy, but it still has many limitations. Chimeric antigen receptormodified T (CAR-T) cells, a novel adoptive immunotherapy strategy, have not only been used successfully against hematological tumors, but have also opened up new avenues for immunotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 122 publications
(190 reference statements)
0
16
0
Order By: Relevance
“…According to the literature, CAR-T cells' most common targeted antigens in NSCLC are EGFR, MSLN, CEA, PD-L1, ROR1, B7H3, MUC1, HER2, and Delta-like ligand 3 (DLL3) [177,[198][199][200][201][202][203][204] (Fig. 3).…”
Section: Lung Cancer (Lca)mentioning
confidence: 99%
“…According to the literature, CAR-T cells' most common targeted antigens in NSCLC are EGFR, MSLN, CEA, PD-L1, ROR1, B7H3, MUC1, HER2, and Delta-like ligand 3 (DLL3) [177,[198][199][200][201][202][203][204] (Fig. 3).…”
Section: Lung Cancer (Lca)mentioning
confidence: 99%
“…Although CAR-T-cell therapies have achieved great success in hematological malignancies, the study of lung cancer is still in the early exploration stage. Numerous clinical trials have progressed slowly and have achieved very limited efficacy, and several challenges and hurdles remain, such as on-target/off-tumor toxicity, CAR-T cell trafficking and infiltration into the tumor, TME heterogeneity, immune suppression, and cytokine release syndrome (224)(225)(226). Recently, Vasic et al (227) found that allogeneic double-negative CAR-T cells inhibit tumor growth with no off-tumor toxicity in either a lung cancer xenograft model or B-cell acute lymphoblastic leukemia (B-ALL) was observed.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…Lung cancer treatments include surgery, chemotherapy, radiotherapy, immunotherapy, neoadjuvant therapy, etc. However, only 20% of patients are suitable for surgery and 80% experience recurrence and eventually die postoperatively [5]. Growing evidence has illustrated that immunotherapy, especially monoclonal antibody-targeted drugs, has been increasingly used in the clinical treatment of lung cancer, among the multifaceted treatment strategies [6].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has illustrated that immunotherapy, especially monoclonal antibody-targeted drugs, has been increasingly used in the clinical treatment of lung cancer, among the multifaceted treatment strategies [6]. In recent years, chimeric antigen receptor-modified T cells (CAR-T cells), as one of the emerging treatment strategies for cancer immunotherapy, have become a new hot spot and focus in the field of cancer therapy research [5,7]. Recently, personalized vaccines that individually select antigens for each patient are being developed [8].…”
Section: Introductionmentioning
confidence: 99%